Nematocera flies recorded in Serra do Courel, northwest Spain, May 2012 (Diptera: Anisopodidae, Blepharoceridae, Cylindrotomidae, Limoniidae, Pediciidae, Tipulidae and Trichoceridae) including descriptions of two new species of Limoniidae - Hancock, E. Geoffrey; Hewitt, Stephen M.; Horsfield, David; Lyszkowsi, Richard M.; Macgowan, Iain; Ricarte, Antonio; Rotheray, Graham E.; Watt, Kenneth (Zootaxa, 2015)
During May 2012 Diptera were sampled in the Serro do Courel area of Lugo Province, Galicia, northwest Spain. The authors of this paper, members of the Malloch Society (see website) are active in attempting to understand the detailed ecology of flies. Much of this work is through targeting larval stages often with an emphasis on saproxylic situations. By rearing adults from larvae direct relationships between them and their detailed habitat requirements are established. The list of nematocerous Diptera that were sampled includes 36 species two of them new to science and records of six others new to the Iberian peninsula are provided. We describe Lipsothrix galiciensis Hancock & Hewitt sp. nov., and Prionolabis pjotri Hancock sp. nov. of the family Limoniidae and provide a key to adults of European Lipsothrix species. Such results from this brief opportunity indicate the potential of the area for further field work in these and other families of Diptera.